Superior organic dye removal by CoCr2O4 nanoparticles: Adsorption kinetics and isotherm - Pham, Kim Ngoc (Elsevier, 2022)
In the present work, we report on the dye removal efficiency of Cobalt chromite, CoCr2O4 nanoparticles synthesized via the solvothermal method. The obtained CoCr2O4 nanoparticles demonstrated that the dye removal efficiency of CoCr2O4 nanoparticles could be enhanced by a reduction of size or improved water dispersibility